From Normal Science to Paradigm Change: A Kuhnian Analysis of Educational Management Theory and Practice - Yusuf Fathurrahman (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2026)
Educational management is increasingly confronted with complex challenges arising from technological transformation, market-oriented governance, ethical crises, and the growing gap between institutional effectiveness and humanistic educational values. These conditions indicate the emergence of anomalies that question the adequacy of the dominant educational management paradigm. This study aims to analyze contemporary educational management through Thomas Kuhn’s concepts of normal science, anomalies, and paradigm change, while exploring the possibility of a more humanistic and prophetic management paradigm. The study employed a qualitative approach with a library research design. Data were collected from primary and secondary scholarly sources and analyzed through data condensation, data display, and conclusion verification. The findings reveal that contemporary educational management functions as a form of normal science characterized by dominant assumptions regarding efficiency, accountability, and performance measurement. However, this paradigm simultaneously generates anomalies, including ethical problems, dehumanization, governance weaknesses, and the marginalization of moral and spiritual dimensions. The accumulation of these anomalies indicates a potential paradigm crisis and the need for transformation toward a humanistic and prophetic educational management model. The implications of this study suggest that educational management should move beyond technocratic and performance-oriented approaches by integrating ethical, humanistic, and prophetic values into institutional governance, leadership, and policy practices.